Inactivation of nitrate reductase alters metabolic branching of carbohydrate fermentation in the cyanobacterium Synechococcus sp. strain PCC 7002. Issue 5 (2nd November 2015) - Qian, Xiao; Kumaraswamy, G. Kenchappa; Zhang, Shuyi; Gates, Colin; Ananyev, Gennady M.; Bryant, Donald A.; Dismukes, G. Charles
ABSTRACT: To produce cellular energy, cyanobacteria reduce nitrate as the preferred pathway over proton reduction (H2 evolution) by catabolizing glycogen under dark anaerobic conditions. This competition lowers H2 production by consuming a large fraction of the reducing equivalents (NADPH and NADH). To eliminate this competition, we constructed a knockout mutant of nitrate reductase, encoded by narB, in Synechococcus sp. PCC 7002. As expected, Δ narB was able to take up intracellular nitrate but was unable to reduce it to nitrite or ammonia, and was unable to grow photoautotrophically on nitrate. During photoautotrophic growth on urea, Δ narB significantly redirects biomass accumulation into glycogen at the expense of protein accumulation. During subsequent dark fermentation, metabolite concentrations—both the adenylate cellular energy charge (∼ATP) and the redox poise (NAD(P)H/NAD(P))—were independent of nitrate availability in Δ narB, in contrast to the wild type (WT) control. The Δ narB strain diverted more reducing equivalents from glycogen catabolism into reduced products, mainly H2 andd ‐lactate, by 6‐fold (2.8% yield) and 2‐fold (82.3% yield), respectively, than WT. Continuous removal of H2 from the fermentation medium (milking) further boosted net H2 production by 7‐fold in Δ narB, at the expense of less excreted lactate, resulting in a 49‐fold combined increase in the net H2 evolution rate during 2 days of fermentation compared to the WT. The absence of nitrate reductase eliminated the inductive effect of nitrate addition on rerouting carbohydrate catabolism from glycolysis to the oxidative pentose phosphate (OPP) pathway, indicating that intracellular redox poise and not nitrate itself acts as the control switch for carbon flux branching between pathways. Biotechnol. Bioeng. 2016;113: 979–988. © 2015 Wiley Periodicals, Inc. Abstract : Metabolic bioengineering of Synechococcus sp. PCC 7002 to reroute electrons towards the synthesis of valuable fermentative products, away from nitrate reduction in the presence of nitrate is described. By eliminating the narB ‐encoded nitrate reductase, Qian and coworkers have significantly elevated the fermentative H2 yield in Synechococcus 7002.